Autoreactive IgE Is Prevalent in Systemic Lupus Erythematosus and Is Associated with Increased Disease Activity and Nephritis - Dema, Barbara; Pellefigues, Christophe; Hasni, Sarfaraz; Gault, Nathalie; Jiang, Chao; Ricks, Tiffany K.; Bonelli, Michael M.; Scheffel, Jörg; Sacré, Karim; Jablonski, Mathieu; Gobert, Delphine; Papo, Thomas; et al. (PloS one, 2014)
The presence of autoantibodies in systemic lupus erythematosus, particularly those of the IgG subclass, have long been associated with disease onset and activity. Here we explored the prevalence of autoreactive IgE in SLE and its relevance to disease in French (n = 79) and United States (US) (n = 117) cohorts with a mean age of 41.5 ± 12.7 and 43.6 ± 15.3 years and disease duration of 13.5 ± 8.5 and 16.6 ± 11.9 years, respectively. Our findings show that approximately 65% of all SLE subjects studied produced IgE antibodies to the seven autoantigens tested. This positivity was increased to almost 83% when only those subjects with active disease were considered. SLE subjects who were positive for anti-dsDNA, -Sm, and -SSB/La -specific IgE showed a highly significant association in the levels of these antibodies with disease activity similar to that of the corresponding IgG's. A strong association of IgE autoantibodies with active nephritis was also found in the combined cohort analysis. A test of the predictive value of autoreactive IgE's and IgGs for disease activity (SLE Disease Activity Index (SLEDAI) ≥ 4) revealed that the best predictors were dsDNA-specific IgE and IgG, and that the age of an SLE subject influenced this predictive model. The finding argue that the overall levels of IgE autoantibodies, independently or in combination with IgG autoantibodies, may serve as indicators of active disease.